2023
DOI: 10.1007/s10098-023-02629-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three typical lithium-ion batteries for pure electric vehicles from the perspective of life cycle assessment

Tingting Jiang,
Huifang Wang,
Qiang Jin

Abstract: In the present study, environmental impacts of lithium-ion batteries (LIBs) has become a concern due the large-scale production and application. The present paper aims to quantify the potential environmental impacts of three LIBs in terms of life cycle assessment (LCA), as well as to identify hotpots and ways to reduce the environmental impacts. Three different batteries are compared in this study: lithium iron phosphate (LFP) batteries, lithium nickel cobalt manganese oxide (NCM) 811 batteries and NCM622 batt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2024
2024
2025
2025

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 63 publications
0
0
1
Order By: Relevance
“…For example, GWP is the lowest in this study, while TETP is the highest by an order of magnitude. Interestingly, the same study (Jiang et al (2023) [74]) that reports the lowest TETP reports an METP that is 10,000 times larger than that found in this study (for the same battery chemistry). Peters et al (2017) [42], in their review of the literature at the time, reported a range of 40 to 250 kg CO 2eq per kWh.…”
Section: Discussioncontrasting
confidence: 50%
“…For example, GWP is the lowest in this study, while TETP is the highest by an order of magnitude. Interestingly, the same study (Jiang et al (2023) [74]) that reports the lowest TETP reports an METP that is 10,000 times larger than that found in this study (for the same battery chemistry). Peters et al (2017) [42], in their review of the literature at the time, reported a range of 40 to 250 kg CO 2eq per kWh.…”
Section: Discussioncontrasting
confidence: 50%